Penetrating cardiac injury - Dublin, N.; Chow, H.K.; Lim, Y.C. (Faculty of Medicine, University of Malaya, 1999)
A case of penetrating cardiac injury is reported where cardiorrhaphy is done without cardiopulmonary bypass and via a right thoracotorny even though median stemotomy is the usual approach. It is also stressed that all precordial stabwounds must be carefully explored.